Peramalan Harga Pasar Telur Ayam Ras di Kota Malang dengan Menggunakan Metode "Fuzzy Time Series-GA" - Eka Miyahil Uyun; Arief Andy Soebroto (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
Awareness of Malang City's people to the consumption of animal protein increased as with the increase level of population growth and living standard. Purebred chicken eggs become one of the preferred animal protein foods because of its cheap price. However, the price of purebred chicken eggs in the market is fluctuating, thus affecting the number of egg demand. Therefore, in this research, a system that can project market conditions is made to determine the market price of purebred chicken in thext period.The data used is the average daily data of the price of purebred chicken eggs in Malang from 2012-2017. This research uses Fuzzy Time Series method for forecasting with GA to find optimal interval value of the fuzzy subsets. The fuzzy subsets are represented by chromosomes with real code value encoding, then they are processed by crossovers, mutations and selection. The crossover, mutation and selection techniques used are one-cut-point crossover, uniform mutation and elitism selection. Based on the test results, the optimal parameters obtained are the population size is 40, chromosome length is 25, the combination of crossover and mutation rate are 0,4 and 0,5, and the number of iterations is 500.The results obtained by applying the optimal parameters indicate that the Fuzzy Time Series-GA method works better than the Fuzzy Time Series. The best MAPE obtained using the Fuzzy Time Series-GA method is 1,3347731.